MERAJUT NILAI KEBHINNEKAAN DENGAN DEEN SALAM SEBAGAI BENTUK RELIGUOUS JOB FOR EDUCATION PEACE DITAHUN POLITIK - M. Sauki; Indra Latif Syaepu (Communicative : Jurnal Dakwah dan Komunikasi, 2020)
Formulating da'wah as a form of actualization of faith that is manifested in an activity is one of the methods or strategies a person uses to convey the message or teaching message. Formulating da'wah can be done in various ways and can use any media, including song lyrics and music. Several years ago, the Indonesian people were shocked by a song performed by Nisya Sabiyan entitled Deen Salam. This song appears right in the midst of community unrest, community divisions or it can be said that Indonesia is experiencing a crisis of harmony. In the song's lyrics, there is a philosophical meaning of the meaning of peace, which is indirectly "religion that carries the message of peace